A Comprehensive Update of Current Anesthesia Perspectives on Therapeutic Hypothermia - Urits, Ivan (Adv Ther, 2019)
Normal thermal regulation is a result of the integration of afferent sensory, central control, and efferent responses to temperature change. Therapeutic hypothermia (TH) is a technique utilized during surgery to protect vital organs from ischemia; however, in doing so leads to other physiological changes. Indications for inducing hypothermia have been described for neuroprotection, coronary artery bypass graft (CABG) surgery, surgical repair of thoracoabdominal and intracranial aneurysms, pulmonary thromboendarterectomy, and arterial switch operations in neonates. Initially it was thought that induced hypothermia worked exclusively by a temperature-dependent reduction in metabolism causing a decreased demand for oxygen and glucose. Induced hypothermia exerts its neuroprotective effects through multiple underlying mechanisms including preservation of the integrity and survival of neurons through a reduction of extracellular levels of excitatory neurotransmitters dopamine and glutamate, therefore reducing central nervous system hyperexcitability. Risks of hypothermia include increased infection risk, altered drug pharmacokinetics, and systemic cardiovascular changes. Indications for TH include ischemia-inducing surgeries and diseases. Two commonly used methods are used to induce TH, surface cooling and endovascular cooling. Core body temperature monitoring is essential during induction of TH and rewarming, with central venous temperature as the gold standard. The aim of this review is to highlight current literature discussing perioperative considerations of TH including risks, benefits, indications, methods, and monitoring.